Effective strategies for teaching listening comprehension in EFL contexts: A systematic review - Angkasa, Gamas Rahma; Noor Farida, Alief (Universitas Negeri Semarang, 2025)
This article examines evidence-based techniques designed to boost listening abilities in learners of English as a foreign language. Although listening underpins most real-world exchanges, many students freeze when speecharkoful is rapid, regional accents appear, or background noise intrudes, slowing their grasp of meaning. Building on current research, the authors single out four classroom techniques–Task-Based Learning, metacognitive training, multimedia input, and peer collaboration–as key to consistent language gains. Moving to technology, they note that podcasts, interactive quizzes, and speech-recognition drills deliver on-demand practice that teachers can quickly adjust to each student's proficiency. The discussion balances cognitive advantages—explaining new processing strategies—with motivational gains, detailing step-by-step ways teachers can blend traditional and digital tools. When these older and newer ideas work together, students have a clearer path past common obstacles and build the listening confidence needed in real-world English. The review ends by offering practical recommendations, helping instructors adopt evidence-based techniques that deepen listening ability and keep learners actively engaged.